Pengaruh Communication Effective dan Reward terhadap Individual Performance - Alfin Renaldi Jakfat Maulana; Wahyu Eko Pujianto (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to examine the influence of Effective Communication and Rewards on Individual Performance in an organizational environment. The research method used is a quantitative approach with a survey technique, involving 80 respondents working in the private sector and selected through purposive sampling. Data collection was carried out using a Likert-scale questionnaire, while data analysis used the Partial Least Square Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4.0 software. The results of the study indicate that both Effective Communication and Rewards have a positive and significant effect on Individual Performance, with Effective Communication having a more dominant influence. These findings emphasize the importance of open communication and providing fair and appropriate rewards as strategies to improve individual performance in organizations.